Direction of isometric ballistic force is related to antagonistic muscule discharge - Mizumura, S.; Maezawa, K.; Ohtsuki, T. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
The purpose of this study was to investigate the relationship between electromyographic (EMG) activities of human thigh muscles (vastus medialis, vastus lateralis, rectus femoris, biceps femoris and semitendinosus) and the direction of knee extension force during ramp and ballistic contractions. Four subjects exerted isometric knee extension forces at a target force level of 40% of maximum voluntary contraction (MVC) at various speeds. Variations of EMG amplitudes of all thigh muscles during ballistic contraction were much larger than those during ramp contractions. Only biceps femoris was related to the direction of force. These results suggest that EMG activity of biceps femoris muscle is an important factor for deciding direction of isometric ballistic knee extension force.